Ingredient variation effects on cookie marketability - Kovaleva Anna; Pyanikova Elvira; Evdokimova Oxana; Galchenko Svetlana; Podieelets Tatiana (E3S Web of Conferences, 2025)
Complete replacement of wheat flour with oat flour prepared from ground oat flakes “Hercules”, oat flour - with oat flakes “Hercules”, eggs - with apple husk, sugar - with topinambour syrup allows to obtain oatmeal biscuits of dietary orientation. The use of these components in the recipe leads to the appearance of two additional technological operations: the first - preparation of oat flour from oat flakes “Hercules”, the second - preparation of a mixture of apple husk, fat component (butter or vegetable oil) and topinambour syrup. The duration of baking of biscuits, compared to the control sample, increased by 7-12 minutes. At the same time, the baking temperature decreased from 180-240°C to 160°C. The introduced changes in the recipe of oatmeal biscuits influenced the organoleptic quality indicators of the finished product. Addition of apple husk to the recipe gave a pleasant fruity taste and aroma of apple raw material to the biscuits. Replacement of sugar with sugar-containing components allowed to obtain a finished product balanced in sweetness. According to physico- chemical parameters the developed samples correspond to the current normative document for this type of products. The recommended shelf life for dietary oatmeal biscuits is 7 days under the storage conditions.